Dental education of left-handed students - Grga Đurica; Miletić Vesna (Serbian Medical Society - Dental Section, Belgrade, 2006)
Introduction: Asymmetrical activity of brain hemispheres is projected through laterality e.g. the dominance of one of the paired organs. A very important way of laterality manifestation is left-handedness. The lef-handed must solve various conflicts with their environment, so mild left-handedness usually shifts into dominant right-handedness in the early childhood, fortunately with no difficulties. Aim: The purpose of this study was to determine the number and distribution of left-handed dental students, check the possibilities and propose measures for solving the problem in their education. Material and methods: The study was conducted at Belgrade University School of Dentistry, dept. of restorative dentistry and endodontics. During two academic years, six generations of senior dental students (III, IV and V year students) completed a questionnaire, i.e. 1385 individuals were included in the survey. Results: The questionnaire revealed that out of the total number or students involved in the study 62 (4.48%) students were left-handed. The distribution of left-handed students is relatively uniform and concentrated between 4-6% of the sample. Conclusion: Even though the number of left-handed students is small, it is necessary to change conditions for their education and enable their proper development.